(untitled) (Jurnal Bahasa, 2018)
Verbs of possession refer to those concerning "belonging". This category of verb also means the transfer of a property (ownership) from one person to another. This article will focus on verbs of possession such as milik (possess), beri (give) and terima (accept) based on conceptual (abstract) point of view. This study utilizes data from the Corpus Data Base of Dewan Bahasa Pustaka as a sample. The analysis employs the Theory of Conceptual Structure of Ray Jackendoff (2005, 2007 & 2011). Semantic representations are described in the form of conceptual structures within Functions [Events] and [States] that carry the conceptual structure formula BE [x, y]. The findings show the representation of the conceptual structure of the verbs represented by the constituents of [BE possession], [GO possession] and [LET possession] in relation to the constituents [THING],[PATH] and [PLACE]. For conceptual structure representation to syntax, data findings indicate a relationship between the Head Rule and Argument Rule based on the role of the argument that becomes a subset of the request and acceptance of verbs to the Name Phrase. Consequently, this study demonstrates the conceptual structure of representation and its relations with systematic syntax, especially concerning verbs of possession. Keywords: verb of possession, conceptual structure, constituents and argument